MODEL EVALUASI STANDAR PELAYANAN PUBLIK SEKTOR KESEHATAN PADA RUMAH SAKIT UMUM DAERAH ATAU PUSAT KESEHATAN MASYARAKAT DI KABUPATEN PACITAN, JAWA TIMUR - Tetuko Rawidyo Putro; Riwi Sumantyo (Jurnal Ekonomi-Qu, 2018)
Regional Public Hospital (RSUD) or Health Centre of Public (PUSKESMAS) is a leading unit in providing public services such as health services to the community of Pacitan. The existence of hospitals in the quality of service is a reflection of the existence of a country, especially related services in the health sector. This study aims to develop a model evaluation of the quality ofpublic services in the health sector. The health sector is a sector that is vital in determining the quality of the generation and the future of a nation. The method used in this research is the Qualitative Response Model (QRM) through Focus Group Discussion with the relevant parties, the management of hospitals, doctors, nurses, clerks and patients. The results of this study areexpected to be a complementary to the public sector, especially in the health sector so that services can be a comprehensive policy in formulating appropriate public policy primarily in the health care sector in public hospital in Pacitan.